A Pediatric Case of Sensory Predominant Guillain-Barré Syndrome Following COVID-19 Vaccination. (January 2022) - Kim, Yunsung; Zhu, Zahra; Kochar, Puneet; Gavigan, Patrick; Kaur, Divpreet; Kumar, Ashutosh
Over six billion doses of Coronavirus Disease 2019 (COVID-19) vaccines have been administered worldwide. Amidst the global COVID-19 vaccination campaign, vaccine-related side effects are of ongoing concern and investigation. According to the Centers for Disease Control and Prevention (CDC) and the United States Department of Health and Human Services, three main conditions in adults have surfaced in association with receiving the COVID-19 vaccines. These include thrombosis with thrombocytopenia syndrome (TTS), a rare syndrome involving venous or arterial thrombosis and thrombocytopenia, Guillain-Barre syndrome (GBS), and myocarditis. While a number of GBS cases in adults have been published, to our knowledge, only one pediatric case of COVID-19 vaccine-related GBS has been reported. Herein we describe a case of sensory predominant GBS following the Pfizer-BioNTech COVID-19 vaccine in a 16-year-old female presenting with bilaterally ascending upper and lower extremity numbness and paresthesia.